2019
DOI: 10.1097/mat.0000000000000792
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal Membrane Oxygenation in a Pediatric Patient with Hepatopulmonary Syndrome and Interrupted Inferior Vena Cava After Living Related Liver Donation

Abstract: Extracorporeal membrane oxygenation (ECMO) is used for cardiopulmonary dysfunction. Hepatopulmonary syndrome (HPS) occurs in the setting of liver failure and may cause hypoxemia. Previous reports have described the use of ECMO for HPS after liver transplant. Our patient is a 19-month-old female with biliary atresia, an interrupted inferior vena cava, and HPS on 8 liters per minute of high-flow oxygen. Following liver transplantation, her postoperative course was complicated by severe hypoxemia requiring ECMO. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…While the numbers were too small to draw any conclusions, we did not note any overt difference in mortality among HPS patients. To corroborate these findings, the limited studies among the pediatric population have revealed good outcomes 18–20 …”
Section: Discussionmentioning
confidence: 85%
“…While the numbers were too small to draw any conclusions, we did not note any overt difference in mortality among HPS patients. To corroborate these findings, the limited studies among the pediatric population have revealed good outcomes 18–20 …”
Section: Discussionmentioning
confidence: 85%
“…reported, with ECMO duration ranging from 17-28 days. 4,7,16 Herein, we describe a pediatric liver transplant recipient with very severe HPS that experienced a delayed decompensation post-LT requiring ECMO support for 91 days with successful decannulation after embolization of a persistent splenorenal shunt. Research on the role of persistent portosystemic shunts following LT in refractory HPS is limited.…”
Section: Discussionmentioning
confidence: 99%
“…Use of ECMO in LT recipients with HPS has been described in the adult population with a demonstrated survival rate of 38%, 3 but the use of this therapy for complications of HPS in the pediatric LT population has not been well established 4‐7 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…From 24 articles initially identified as potentially eligible, 16 studies were retrieved for data extraction after fulltext review (Figure 2). The studies included in the present systematic review were published between 2000 and 2020 and were conducted in the United States (n = 7), 8,9,[18][19][20][21][22] Asia (n = 5), 7,12,[23][24][25] Europe (n = 3), [4][5][6] and Canada (n = 1). 26 A total of 22 children that received ECMO on the day of transplant or later were included in the systematic review (Table 4).…”
Section: Systematic Review Of the Literaturementioning
confidence: 99%